2018
DOI: 10.4187/respcare.05965
|View full text |Cite
|
Sign up to set email alerts
|

Airway Clearance With an Optimized Mechanical Insufflation-Exsufflation Maneuver

Abstract: The optimized MI-E maneuver, applied with slow insufflation, resulted in a higher expiratory flow bias, which made the therapy more effective at moving mucus outward, compared with the standard MI-E maneuver, typically applied with fast insufflation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 31 publications
1
35
0
Order By: Relevance
“…A recent study found that mucus transport could be further enhanced by applying a slow insufflation, which created a greater expiratory flow bias. 10 Despite this evidence base, some centers reported an increase in CPF with low pressures, [11][12][13][14] whereas others have reported efficacy with high pressures. [15][16][17][18][19][20] Hov and coworkers 21 surveyed centers in Europe and found that younger children were set up with lower MI-E pressures than older children and that there was wide variation in settings prescribed.…”
Section: See the Related Editorial On Page 265mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study found that mucus transport could be further enhanced by applying a slow insufflation, which created a greater expiratory flow bias. 10 Despite this evidence base, some centers reported an increase in CPF with low pressures, [11][12][13][14] whereas others have reported efficacy with high pressures. [15][16][17][18][19][20] Hov and coworkers 21 surveyed centers in Europe and found that younger children were set up with lower MI-E pressures than older children and that there was wide variation in settings prescribed.…”
Section: See the Related Editorial On Page 265mentioning
confidence: 99%
“…This is also likely to contribute to an expiratory air-flow bias because our exsufflation pressures were greater than our insufflation pressure. However, with new evidence emerging from both a bench study, 10 and flexible transnasal fiber-optic laryngoscopy during MI-E, 29,30 it is clear that more attention needs to be paid to insufflation flow and insufflation pressures. A key implication for clinicians is that some bulbar ALS patients are unlikely to benefit from high pressures and flows and may not tolerate MI-E if they have spasticity of the upper airway.…”
Section: Significance Of Findingsmentioning
confidence: 99%
“…However, adjusting high inspiratory flow might not be indicated in mechanically ventilated patients because it might reduce the expiratory flow bias and, consequently, the efficacy of clearing secretion. This likelihood was demonstrated by Volpe et al 74 in a bench study with a lung model simulating a patient on mechanical ventilation. The authors reported that the MI-E maneuver was optimized by applying slow lung insufflation, which reduced the PIF and, consequently, increased the expiratory flow bias (Fig.…”
Section: Mechanical Insufflation-exsufflationmentioning
confidence: 72%
“…Moreover, the authors noted that the expiratory flow bias (PEF -PIF difference) and MI-E pressure gradient were significantly correlated with mucus displacement, whereas the PEF was not. 74 These results indicate that, to optimize airway Time (s) A B Fig. 4.…”
Section: Mechanical Insufflation-exsufflationmentioning
confidence: 85%
“…There are some practical limitations in the study by Volpe et al 5 The reproducibility to achieve the low insufflation flow manually has not been evaluated. It could be speculated as being low in the daily practice according to the way that the authors changed the insufflation flow with the model CM-3200 (Philips Respironics, Murrysville, Pennsylvania).…”
Section: Mechanical Insufflation-exsufflation: Room For Improvementmentioning
confidence: 99%